Eurasia 2.0 : Russian geopolitics in the age of new media - Bassin, Mark; Suslov, M. G. (Russian, Eurasian, and Eastern European politics., 2016)
This book discusses the return of geopolitical ideas and doctrines to the post-Soviet space with a special focus on the new phenomenon of digital geopolitics, an overarching term for different political practices including dissemination of geopolitical ideas online, use of the Internet by political figures and diplomats for legitimation and outreach activity, and viral spread of geopolitical memes. Different chapters explore and consider the new possibilities and threats associated with this digitalization of geopolitical knowledge and practice, new spatial sensibilities, and identities of global as well as local selves. Developing Manuel Castells's argument that social activism in the digital era is organized around cultural values, these chapters discuss new geopolitical ideologies which aim to reinforce Russia's spiritual sovereignty as a unique civilization, while at the same time seeking to rebrand Russia as a greater soft power by utilizing the Russian-speaking diaspora or employing traditionalist rhetoric. Given the political events of recent years, it is logical that the Ukrainian crisis should provide the thematic backdrop for most of the authors.